2007
DOI: 10.1111/j.1532-5415.2007.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Education and Individualized Counseling in Reducing Environmental Hazards in the Homes of Community‐Dwelling Older Women

Abstract: Education and counseling have only modest effects in helping older women make recommended home modifications. To be most effective in reducing environmental hazards, fall prevention programs may need to provide and install safety devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
(72 reference statements)
0
26
0
1
Order By: Relevance
“…The methods used in this study have been described elsewhere. 40,41 Only data on the participants randomized to the fall prevention program are included in this analysis because that group received exercise adoption instruction. Participants were recruited through letters mailed to a population-based sample of female Medicare enrollees.…”
Section: Design and Samplementioning
confidence: 99%
“…The methods used in this study have been described elsewhere. 40,41 Only data on the participants randomized to the fall prevention program are included in this analysis because that group received exercise adoption instruction. Participants were recruited through letters mailed to a population-based sample of female Medicare enrollees.…”
Section: Design and Samplementioning
confidence: 99%
“…Participants were excluded if they had an artificial leg or leg brace; were involved in regular exercise for 3 or more days per week; had unstable health problems prohibiting safe, independent exercise; were terminally ill; or had poor corrected near visual acuity ≥ 20/70. There were 4,112 women assessed for eligibility, 41% did not respond to recruitment efforts, 29% were ineligible, 23% refused participation, and 7% enrolled in the study (Wyman et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Environmental hazards could be a cause of falls (Lord et al, 2007). In reducing environmental hazards, falls prevention programs may need to provide and install safety devices particularly in the homes (Wyman et al, 2007). Studies have shown that when older patients at increased risk of falls are discharged from the hospital, a facilitated environmental home assessment should be considered (AGS, BGS, AAOS, 2001;Tinetti, 2003).…”
Section: Clinical Trials and Multifactorial Interventionmentioning
confidence: 99%